2015
DOI: 10.1016/j.clinph.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of vestibular evoked myogenic potentials: Data from the Baltimore Longitudinal Study of Aging

Abstract: Objective To evaluate whether age-related changes in vestibular evoked myogenic potentials (VEMPs) differ by demographic and cardiovascular risk groups. Methods Participants in the Baltimore Longitudinal Study of Aging underwent cervical and ocular VEMP testing. VEMP latency, amplitude, asymmetry ratios, and prevalence of absent responses were compared across demographic and cardiovascular risk groups. Results In 257 participants (mean age 72.9, 57% female), ocular VEMP (oVEMP) n10 latency increased by 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 35 publications
9
96
0
1
Order By: Relevance
“…Further, a more recent study by Li et al in 257 subjects demonstrated that with aging, there was a reduction in oVEMP amplitude by 2.9 µV per decade of life and an increase in latency of 0.12 ms per decade of life. With respect to cVEMP, they found that the amplitude decreased by 0.14 µV per decade but found no significant difference in latency between the age groups (30). …”
Section: The Peripheral Vestibular Systemmentioning
confidence: 96%
“…Further, a more recent study by Li et al in 257 subjects demonstrated that with aging, there was a reduction in oVEMP amplitude by 2.9 µV per decade of life and an increase in latency of 0.12 ms per decade of life. With respect to cVEMP, they found that the amplitude decreased by 0.14 µV per decade but found no significant difference in latency between the age groups (30). …”
Section: The Peripheral Vestibular Systemmentioning
confidence: 96%
“…We have previously documented an association between vestibular loss and aging in this population (4, 5). In this study, we specifically examined whether VOR gain, compensatory saccade amplitude, and latency were associated with performance on the Short Physical Performance Battery (SPPB).…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, it necessary for each laboratory to gather its own normative database from which pathological outcomes can be evaluated. This database should contain VEMP responses of healthy subjects of varying age groups, since both cVEMPs and oVEMPs show reduced outcomes with increasing age [153,154]. …”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%